(untitled) (Archaeologia Adriatica, 2021)
Late Antiquity, known as a transitory phase between Antiquity and the Middle Ages that encompasses the 4th-6th centuries, was characterized by major historical events that led not only to political and administrative changes, but also social, cultural and religious changes. This paper will elaborate the impact of these changes in the province of Dardania, of which the central territory corresponds to today’s Kosovo, with a specific focus on the spread of Christianity and Christian architecture and changes in settlement patterns, as people moved from field settlements to hillforts. Moreover, it will present architectural features and the role of fortifications in Late Antiquity.